Asuhan Keperawatan Pada Tn.I Dengan Halusinasi Penglihatan Di RSJ Tampan Provinsi Riau Tahun 2024 - Chandra Hermawan; Yenny Safitri (LPPI Yayasan Almahmudi Bin Dahlan, 2025)
Hallucinations are one of the symptoms of mental disorders where the client experiences changes in sensory perception, feeling false sensations in the form of sound, sight, taste, touch, or smell, the client feels a stimulus that does not actually exist. The factors that cause hallucinations are divided into two, namely predisposing factors related to biological, psychological, socio-cultural, environmental. and precipitation factors related to a history of infectious diseases, chronic diseases or structural abnormalities of the brain, a history of violence in the family, or a history of failures in life, and poverty. The purpose of this study was to examine to carry out nursing care for Mr.I with visual hallucinations in the Sebayang room of Tampan Mental Hospital, Riau Province. The research design used in this research is a case study. The subject of the case reports is Mr.I who is 43 years old with visual hallucination disorder. Data obtained by interview, observation, physical examination, and documentation study. At the time of assessment, the patient said he saw a black shadow in the form of a person seen in the morning, afternoon and evening. When the patient saw the shadow told the patient to climb the wall. So that researchers can formulate the main problem with the diagnosis of visual hallucinations. Nursing actions taken on Mr.I with visual hallucinations are carried out according to the nursing plan that has been prepared. The results of nursing visits for five days on clients have been obtained with resolved problems. The nursing evaluation stage with SOAP obtained problems resolved and planning maintained. The hope of researchers from writing this case report is to become a good guide for agencies, communities and further researchers.